2008
DOI: 10.4072/rbp.2008.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Middle Devonian chitinozoan biostratigraphy and sedimentology in the eastern outcrop belt of the Parnaíba Basin, northeastern Brazil

Abstract: This paper presents the first account of palynomorphs (chitinozoans) from the eastern outcrop belt of the Parnaiba Basin. The chitinozoans are obtained from shallow well core samples, penetrating the Pimenteira Formation, and indicate a late Eifelian-early Givetian age span for this stratigraphic unit, suggesting the absence of a 3 rd order unconformity. On the other hand, six minor forced regression unconformities (4 th /5 th order) occur in the Pimenteira Formation (sequences C-H by Young & Borghi, 2006). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
(20 reference statements)
0
8
0
1
Order By: Relevance
“…Bergamaschi and . Similar conditions are known from the Parnaíba Basin (Grahn et al, 2008). The latest Emsian Tibaji Member of the Ponta Grossa Fm.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Bergamaschi and . Similar conditions are known from the Parnaíba Basin (Grahn et al, 2008). The latest Emsian Tibaji Member of the Ponta Grossa Fm.…”
Section: Discussionmentioning
confidence: 57%
“…A minor gap is probably present at this level (cf. Grahn et al, 2008). The chitinozoan species Ancyrochitina varispinosa can be used as an index species for latest Emsian -late early Eifelian strata, from where the Alpenachitina eisenacki Zone marks the rest of Chapada unit 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the Parnaíba Basin the chitinozoan Alpenachitina eisenacki is found in both sequences C and D, whereas Ancyrochitina flexuosa is restricted to sequence C and Fungochitina pilosa is found only in sequence D. These species occur in the Playa del Tranqueru section in this same sequential order, with F. pilosa first appearing about 27 m above A. flexuosa (Askew & Russell 2019). Grahn et al (2008) indicated the Eifelian-Givetian boundary as being at the boundary between sequences C Figures 4-6. Filled symbols represent locations with multiple assemblages very close to one another.…”
Section: Sea-level Changementioning
confidence: 94%
“…A further Brazilian scheme describes regressions at an even finer scale of fourth-fifth order, described as 'minor forced regression unconformities' (Young 2006;Young & Borghi 2006). This sequence stratigraphic analysis has been applied in late Eifelianearly Givetian rocks in the Parnaíba Basin that contain abundant palynomorphs, allowing potential marker species to be identified (Grahn et al 2008). Again, the rocks studied here can be likened on purely lithological grounds to the sandy sequence B followed by the much finer grained sequences C and D above.…”
Section: Sea-level Changementioning
confidence: 99%
“…Lange (1967) briefly mentioned chitinozoans from the Parnaíba Basin, and Cruz and Quadros (1985) described a new chitinozoan species from the latest Frasnianearly Famennian. More recently, chitinozoans have been discussed and correlated with miospores in papers by Grahn and Melo (2005), Grahn et al (2001Grahn et al ( , 2006Grahn et al ( , 2008 and Breuer and Grahn (2011). The Pimenteiras Formation consists of a lower Middle Devonian section, separated by a hiatus from the upper Late Devonian section.…”
Section: Chitinozoansmentioning
confidence: 99%